Benefits finding among Chinese family caregivers of stroke survivors: a qualitative descriptive study. Issue 10 (19th October 2020) - Mei, Yong-Xia; Lin, Beilei; Zhang, Weihong; Yang, Dong-Bin; Wang, Shan-Shan; Zhang, Zhen-Xiang; Cheung, Daphne Sze Ki
Abstract : Objectives: The caregiving experience includes both caregiver burdens and benefits finding. However, the benefits obtained by family caregivers of stroke survivors in Chinese community dwellings are unknown. The objective of this study was to explore the benefits experienced by family caregivers of stroke survivors in Chinese community dwellings. Design: A qualitative descriptive design was used, fulfilling the consolidated criteria for the Standards for Reporting Qualitative Research reporting guidelines. Semi-structured interviews were conducted with 20 family caregivers of stroke survivors. The interviews were audiotaped, transcribed and analysed. Thematic analysis was performed to analyse the interview transcripts. Setting and participants: Home interviews were conducted with family caregivers of stroke survivors in two communities in Zhengzhou, China. Results: The family caregivers of stroke survivors experienced various benefits from caregiving. There were both internal benefits (increases in knowledge and skills, the development of positive attitudes, and the development of a sense of worthiness and achievement) and external benefits (family growth and gains in social support), which interact to create a healthy lifestyle. Conclusion: Our findings provide a comprehensive perspective in understanding the benefits perceived by family caregivers of stroke survivors. This study provides insights into interventions focused on identifying benefits finding in six domains that may help reduce negative emotions and promote the mental health of caregivers.